Policy intervention in debt renegotiation: Evidence from the Home Affordable Modification Program - Sumit Agarwal; Gene Amromin; Itzhak Ben-David; Souphala Chomsisengphet; Tomasz Piskorski; Amit Seru (Federal Reserve Bank of Chicago, 2013)
The main rationale for policy intervention in debt renegotiation is to enhance such activity when foreclosures are perceived to be inefficiently high. We examine the ability of the government to influence debt renegotiation by empirically evaluating the effects of the 2009 Home Affordable Modification Program (HAMP) that provided intermediaries (servicers) with sizeable financial incentives to renegotiate mortgages. A difference-in-difference strategy that exploits variation in program eligibility criteria reveals that the program generated an overall increase in the intensity of renegotiations while adversely affecting the effectiveness of renegotiations performed outside the program. Renegotiations induced by the program resulted in a modest reduction in the rate of foreclosures and reached just one-third of its targeted 3 to 4 million indebted households. This shortfall is in large part due to low renegotiation intensity of a few large servicers that responded at half the rate than others. The muted response of these servicers - which is also observed before the program - does not reflect differences in contract, borrower, or regional characteristics of mortgages across servicers. Instead, it reflects servicer-specific factors that appear to be related to their preexisting organizational capabilities. We exploit regional variation in the share of loans serviced by intermediaries with high pre-program renegotiation activity to assess the economic effects in areas more exposed to the program. Regions where HAMP was used intensively saw a lower rate of house price decline as well as an increase in the pay-down rate on consumer debt. There was no change in non-durable and durable consumption in these regions, suggesting that distressed borrowers who are in the process of debt deleveraging may have a relatively low spending multiplier from moderate debt reduction. We conclude by discussing implications of our findings for debt relief programs in general and for other policy responses to crises that also require intermediaries for implementation.
Keywords: E60; E65; G18; G21; H3; 330; Government intervention; Debt renegotiation; Mortgage modification; Foreclosures; Housing crisis; HAMP; Servicers